Zakat Literacy: Digital Islamic Finance in Community Economic Development - Damirah, Damirah; Sahrani, Sahrani; Musmulyadi, Musmulyadi (Universitas Trunojoyo Madura, 2024)
The purpose of this study is to explore the pivotal roles of Islamic finance and Zakat, particularly in the context of digital transformation, in improving financial literacy and fostering economic growth within communities. The study specifically examines how the digitalization of Zakat collection and distribution, alongside other Islamic finance principles, contributes to the development of an inclusive and ethical economy rooted in Islamic values.This study employs a mixed-method approach, combining qualitative and quantitative analyses. Data is gathered through interviews, case studies, and statistical analysis to explore the impact of digital Islamic finance and Zakat management on community economic development. The study focuses on how digital literacy in Islamic finance, particularly Zakat, can enhance economic outcomes and the effectiveness of these tools for poverty alleviation.The study reveals that integrating Islamic finance and Zakat with digital technology significantly improves financial literacy, leading to better economic decision-making and sustainable economic development. The digitalization of Zakat processes not only increases transparency and efficiency but also broadens the reach and impact of Zakat, reinforcing its role as a crucial instrument in Islamic finance for poverty alleviation. However, key challenges, such as gaps in public understanding and limited access to financial education, need to be addressed to fully leverage the potential of digital Islamic finance and Zakat.